Analisa Kepuasan Kerja, Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Widyaiswara Melalui Etos Kerja di Lingkungan Badan Pendidikan dan Pelatihan Kementerian Pertahanan (Badiklat Kemhan) - Sutarmi Sutarmi; Slamet Ahmadi (Syntax Idea)
Human Resource Management (HRM) plays a crucial role in the administration of personnel within an organization, focusing on planning, organizing, training, and compensation management. Employee performance is a critical aspect that influences the goals of a company. This research focuses on the Education and Training Agency of the Ministry of Defense (Badan Pendidikan dan Pelatihan Kementerian Pertahanan or Badiklat Kemhan), specifically on the performance of Widyaiswara, a key element in the outcomes of education and training. The research design follows the framework of Grenner and Martelli, with an emphasis on explanatory research that focuses on the relationship between research variables and tests hypotheses. This study aims to identify the impact of HRM policies and decisions on employee performance, with a focus on workplace relationships, cohesion, and harmony. The implications of this research can serve as practical guidance for civil servants, especially those in Badiklat Kemhan and other government agencies. The findings of this research can be used as a reference to enhance the efficiency and effectiveness of employee performance by improving job satisfaction through the enhancement of work ethics, organizational culture, and organizational commitment.